2010
DOI: 10.4103/0019-5413.62083
|View full text |Cite
|
Sign up to set email alerts
|

Iso-C3D navigation assisted pedicle screw placement in deformities of the cervical and thoracic spine

Abstract: Background:Pedicle screw instrumentation of the deformed cervical and thoracic spine is challenging to even the most experienced surgeon and associated with increased incidence of screw misplacement. Iso-C3D based navigation has been reported to improve the accuracy of pedicle screw placement, however, there are very few studies assessing its efficacy in the presence of deformity. We conducted a study to evaluate the accuracy of Iso-C3D based navigation in pedicle screw fixation in the deformed cervical and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Different navigation systems were used, including StealthStation [ 12 , 17 ], VectorVision [ 18 , 19 ] and intraoperative CT [ 10 , 20 ]; both were included. The trials involving templates used Mimics Software to design the template from pre-operative scans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different navigation systems were used, including StealthStation [ 12 , 17 ], VectorVision [ 18 , 19 ] and intraoperative CT [ 10 , 20 ]; both were included. The trials involving templates used Mimics Software to design the template from pre-operative scans.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-operative registration navigation was previously held back by prolonged intraoperative registration that had to be performed for each vertebrae, extending intraoperative times. Rajan reported on over 340 pedicle screws and showed that average insertion time was 2.37 min, whilst the registration time was 24.6 min [ 18 ]. Yang compared 210 pre-operatively registered and navigated pedicle screws with 152 fluoroscopic lumbar spine pedicle screws and noted 3.65 min per screw in the navigated group and 4.43 min in the fluoroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies documented pedicle screw breach rates ranging from 10% to 15% using free-hand or fluoroscopic techniques [Table 3]. [2,4,6,7] Literature also shows significant pedicle breach with navigation aid; i.e., Schwarzenbach et al [8] and Rajan et al [5] showed 11% pedicular breach rates. Rampersaud et al [7] showed a 15% pedicular breach rate, while Merloz et al [4] showed a 10% of pedicular breach rate.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional fluoroscopy and navigation systems improve the accuracy of pedicle screw insertion [20]. Cone-beam type CT is also being increasingly used for difficult procedures, such as cervical pedicle screw placement [21].…”
Section: Discussionmentioning
confidence: 99%